2022
DOI: 10.1249/jes.0000000000000300
|View full text |Cite
|
Sign up to set email alerts
|

The Nervous System as a Pathway for Exercise to Improve Social Cognition

Abstract: The promotion of autonomic balance and social brain networks may explain the association of endurance exercise and social cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The few available studies in autistic children also found acute exercise‐induced improvements in executive function (Anderson‐Hanley et al, 2011; Ringenbach et al, 2015). In an evolutionary model, it has been hypothesized that this effect may translate to social‐cognitive abilities based on a high proportion of overlapping neural substrates with executive function (Ludyga et al, 2022). On a behavioral level, experimental findings support this theory by improvements in facial emotion recognition among healthy children following moderately‐intense aerobic exercise (Brand et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The few available studies in autistic children also found acute exercise‐induced improvements in executive function (Anderson‐Hanley et al, 2011; Ringenbach et al, 2015). In an evolutionary model, it has been hypothesized that this effect may translate to social‐cognitive abilities based on a high proportion of overlapping neural substrates with executive function (Ludyga et al, 2022). On a behavioral level, experimental findings support this theory by improvements in facial emotion recognition among healthy children following moderately‐intense aerobic exercise (Brand et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Third, our study focused primarily on the function of the LPFC; however, other regions involved in the empathy and mentalizing network, such as the temporal-parietal junction and posterior cingulate cortex, also contribute to human prosocial behaviour. 18 Recent findings suggest that exercise can enhance social brain network function, 65,66 thereby suggesting the role of these additional regions in this association. Future studies should incorporate other imaging methods, such as fMRI, to explore the involvement of these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Social behaviors such as affectionate touch and physical proximity are known to stimulate oxytocin secretion (Burenkova et al, 2023; Caicedo Mera et al, 2021; Holt-Lunstad et al, 2008; Landgraf and Neumann, 2004). Light-intensity acute exercise has been shown to enhance mood and prosocial skills in healthy individuals (Basso and Suzuki, 2017; Edwards et al, 2017; Ludyga et al, 2022), with oxytocin believed to partially mediate these effects (Ludyga et al, 2022). Moreover, even brief 10-minute exercise sessions have been shown to elevate salivary oxytocin levels (de Jong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise offers numerous benefits, including disease prevention and the treatment of psychiatric disorders such as depression and anxiety disorders (Deslandes et al, 2009; Hwang et al, 2023; Laird et al, 2023; Viana & de Lira, 2020). Even light-intensity acute exercise has been shown to enhance mood and prosocial skills in healthy individuals (Basso & Suzuki, 2017; Edwards et al, 2017; Ludyga et al, 2022). These effects of exercise are believed to be partially mediated by oxytocin (Ludyga et al, 2022), as evidenced by reports indicating that brief 10-minute exercises increase salivary oxytocin levels (de Jong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation